Revealing missing charges with generalised quantum fluctuation relations - J. Mur-Petit (Nature Portfolio, 2018)
Conservation laws are a key ingredient in the non-equilibrium dynamics of quantum many-body systems. Here, the authors develop generalised quantum fluctuation relations in order to identify the presence of conserved quantities relevant for a generalised Gibbs ensemble.